Awareness and healthcare-seeking behavior regarding acute respiratory infections among mothers of under-five children in rural Tamil Nadu: A hospital-based cross-sectional study - Rasha Aslam Koranath; Abhilasha Nair (Journal of Current Research in Scientific Medicine)
Background: Acute respiratory infection (ARI) is one of the leading causes of morbidity and eventually mortality in under-five children across the globe. Awareness regarding ARI among mothers of these children is very essential to detect danger signs early, prevent the delay in health-seeking and thereby limiting its progression to severe illness. The present study was undertaken to assess the awareness of mothers regarding ARI in their under-five children and their healthcare-seeking behavior for the same. Materials and Methods: The present cross-sectional study was carried out among 200 mothers of under-five children attending the outpatient department of a rural health center in Tamil Nadu. A predesigned questionnaire was used to assess their sociodemographic characteristics, awareness about ARIs, and healthcare-seeking behavior regarding ARIs in under-five children. Descriptive and inferential statistics were applied for data analysis. Results: The mean awareness score (±standard deviation) of mothers regarding ARI in their under-five children was 8.34 ± 1.49, and overall, 94.50% of mothers had fair awareness regarding ARI. The association between occupation and awareness level of mothers regarding ARI was found to be statistically significant, while that of other variables was not statistically significant. Most of the mothers (88.0%) preferred to consult a qualified allopathic doctor for their child’s ARI. Those who do not seek health-care services for their child’s illness believe that the disease is self-limiting, while others try traditional medicines at home before seeking health-care services. Conclusion: Majority of mothers had fair awareness regarding childhood ARI in this study. It is necessary to put more effort into educating these mothers about the importance of early detection and seeking appropriate health care for ARI in their children.